1991
DOI: 10.1095/biolreprod44.3.425
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Prolactin Perfusion Induces Incubation Behavior in Turkey Hens1

Abstract: Intracranial perfusion of ovine prolactin (oPrl) via osmotic pump in laying turkey hens caused a sudden onset in incubation behavior, defined as an increase in nest visits. The hens also displayed a gradual decrease in egg laying during the time they were receiving oPrl, another indicator of the onset of incubation. Circulating immunoreactive turkey Prl levels fell during the perfusion period, even though the hens were displaying persistent nesting activity and reduced egg laying. No effects on serum LH were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 8 publications
6
38
1
2
Order By: Relevance
“…Recently, Huang et al [47] reported a negative correlation between inhibin and LH during the reproductive cycle in Magang geese. It is well known that prolactin plays the most important role in the timing and duration of incubation behaviour in broody birds [48][49][50][51]. In the present study, prolactin secretion markedly changed during the reproductive cycles of the turkey hens.…”
Section: Discussionsupporting
confidence: 44%
“…Recently, Huang et al [47] reported a negative correlation between inhibin and LH during the reproductive cycle in Magang geese. It is well known that prolactin plays the most important role in the timing and duration of incubation behaviour in broody birds [48][49][50][51]. In the present study, prolactin secretion markedly changed during the reproductive cycles of the turkey hens.…”
Section: Discussionsupporting
confidence: 44%
“…A role for prolactin in avian parental behaviour was first reported as early as 1935 when injections of prolactin into domestic fowls were found to induce broodiness and egg incubation behaviours [21]. Increased parental behaviours have been shown after exogenous prolactin administration in willow ptarmigan, Lagopus l. lagopus [22], and in turkeys, Meleagris gallopavo [23].…”
Section: Infant Care and Prolactin Secretion In Cooperatively Breedinmentioning
confidence: 99%
“…On October 9, 1998, we changed the photoperiod to 10L 14D and stepped it by 2-h intervals each week to 14L 10D. On egg-day 2, we subcutaneously implanted in the scapular region of each female (without anesthesia) an osmotic pump (model 1002: Alza Corporation, Palo Alto, CA) containing ovine (as opposed to avian) prolactin (NIDDK oPRL-21) because previous studies have shown the readily available ovine prolactin (oprolactin) to be effective in birds (Pedersen, 1989;Youngren, El Halawani, Silsby, and Phillips, 1991) and to bind specifically to crude membrane fractions of ring dove, Streptopelia risoria, brain homogenates (Buntin and Ruzycki, 1987). Each pump contained 100 l of one of three o-prolactin concentrations and pumped at a rate of 0.28 l/h.…”
Section: Laboratory Studiesmentioning
confidence: 99%